Effect of Notice of Tax Warning, Notice of Tax Collection, and Tax Education Programs on Tax Compliance in West Sumatera and Jambi - Indra Budiman; Inayati Inayati (Universitas Muhammadiyah Gorontalo, 2021)
This research examines the two components of the Slippery Slope framework, power, and trust, in influencing formal tax compliance in the West Sumatera and Jambi region. The supervision factors: Notice of Tax Warning and Notice of Tax Collection are used as a proxy of power, and public education program is used as a proxy of trust in the authority. Secondary data collected through documentation study is presented in panel data and then analyzed using panel data regression analysis. As this study uses a mixed quantitative and qualitative method, we conducted in-depth interviews with key informants to get a more robust analysis. This study shows that together and partially, these three factors have a positive and significant effect on formal tax compliance. Notice of Tax Warning and Notice of Tax Collection effectively deliver law enforcement's message as a coercive power through supervision efforts. At the same time, tax education programs are practical to encourage awareness and trust in the authority that ultimately improves tax compliance. This study recommends some improvements in administrative issues and strategies to reach more taxpayers, perform more fair treatment, and enhance compliance.